Development of bacteria-based bioorganic phosphate fertilizer enriched with rock phosphate for sustainable wheat production - Aslam, Zoya; Yahya, Mahreen; Hussain, Hafiz Shahid; Tabbasum, Saira; Jalaluddin, Sabahet; Khaliq, Shazia; Yasmin, Sumera (Frontiers in Microbiology, 2024)
Phosphorous (P) is a limiting macronutrient for crop growth. Its deficiency prevents plant development leading to an extensive use of phosphatic fertilizers globally. Bio-organic phosphate (BOP) fertilizer provides a sustainable approach to optimize nutrient availability, enhance crop yield, and mitigate the negative impacts of chemical fertilizers on the environment. Therefore, the present study integrates the application of heat-tolerant phosphate-solubilizing bacteria, rock phosphate, and organic materials for the development of BOP. For this purpose, potential heat-tolerant phosphate-solubilizing bacteria (PSB) were isolated from major wheat-growing areas of southern Punjab. Five isolates were the efficient phosphate solubilizers based on in vitro phosphate-solubilizing activity (291–454 μg ml−1 and 278–421 μg ml−1) with a concomitant decrease in pH (up to 4.5) at 45°C and 50°C, respectively. These PSB were used for the development of potential consortia that are compatible and showed high P solubilization. In planta evaluation of these PSB consortia in a pot experiment under net house conditions showed that consortium-2 had a favorable impact on growth parameter with enhanced grain yield (9.63 g plant−1) and soil available P (10 μg g−1) as compared with 80% uninoculated control. The microcosm study was conducted to evaluate PSB consortium-2 integrated with carrier material (plant material and filter mud) and rock phosphate as BOP increased total phosphorous (14%) as compared with uninoculated controls. Plant-based BOP showed higher viable count (3.5 × 10800B0CFU) as compared with filter mud-based BOP. Furthermore, the effect of BOP on wheat growth parameters revealed that BOP showed a promising influence on grain yield (4.5 g plant−1) and soil available P (10.7 μg g−1) as compared with uninoculated 80 and 100% controls. Principle component analysis (PCA) further validates a positive correlation between BOP with grain weight and plant height and soil available P as compared with both 80 and 100% controls. For the first time, this study reports the combined application of bio-organic phosphate fertilizer and heat-tolerant PSB, which offers an eco-friendly option to harvest better wheat yield with low fertilizer input.